Estudio de algoritmos de filtrado basado en contenidos para sistemas recomendadores de in formación. - Pacheco Pazmiño, Henry Wladimir (2018)
The filtering algorithms have a content that contains the most advanced information that is presented in the most frequent way in the personalization of content in a register of records of a user who received a subsequent search, since it obtains an immensity that does not require or does not he agree with found finds, losing interest in continuing to use the application. Classification systems are based on content algorithms that are used to detect the most important elements in the world, to be able to receive the interests of users for its subsequent implementation generating a help to perform tasks effectively. By means of the last investigation of the information filtering algorithms in content, it demonstrates the great benefit that people make software practices in order to obtain their suggestions in an appropriate way and with prompt consultation. This document allows to obtain a representation of the information filtering systems in which the multiple aspects are used in information filter, which presents the means to obtain answers of useful information the user. For the results, the logic of four information filtering algorithms is compared with the content, which demonstrates how they work through the development and visualization of the application on the web. The impacts are in the present project show the great interest to continue the investigation for the future implantation in information software that contribute part, to the user with the use of what he needs and with the companies his economic income. Is possible to establish algorithms that help the easy handling for specific content in computer applications, being very useful for the user's interaction with the system, it is recommended the implementation of these algorithms in systems within the university with the which will enhance learning, experience and user satisfaction.